2008
DOI: 10.1177/039463200802100118
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Interferon Response Genes and of Plasmacytoid Dendritic Cells in HIV-1 Positive Subjects with GB Virus C Co-Infection

Abstract: GB virus C (GBV-C) coinfection has a protective role in Human Immunodeficiency Virus (HIV) infection, and increases the duration of suppression of HIV-1 viremia in patients under Highly Active Anti-Retroviral Therapy (HAART). Since innate antiviral response may be involved in the protection, we analyzed the possible role of GBV-C as activator of innate immunity. To this aim, we measured the extent of activation of the interferon (IFN) system and of circulating Dendritic Cells (DC) in vivo, and the ability of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…In that study, researchers also found an intermediate protective role for antibodies specific for the E2 protein of GBV-C. Studies conducted in the highly active antiretroviral therapy (HAART) era have demonstrated that GBV-C is associated with lower rates of HIV rebound after HAART-driven virological success (Antonucci et al 2005, Souza et al 2006. Several mechanisms have been proposed to explain the putative effect of GBV-C on the course of HIV disease, such as increased secretion of the chemokines regulated on activation, normal T cell expressed and secreted (Nattermann et al 2003), macrophage inflammatory protein (MIP)-1α, MIP-1β and stromal cell-derived factor-1, reduced expression of the chemokine receptors CCR5 and CXCR4 (Xiang et al 2004), preservation of the Th1 cytokine profile (Sathar et al 2004), activation of the interferon (IFN) gene system (Capobianchi et al 2006), increased frequency of plasmacytoid dendritic cells expressing CD80 (Lalle et al 2008) and decreased T cell activation (Maidana-Giret et al 2009). In contrast, other studies have failed to demonstrate an influence of GBV-C on the course of HIV infection (Quiros-Roldan et al 2002, Jung et al 2005, Van der Bij et al 2005, Haji Molla Hoseini et al 2007), while at least one report concluded that GBV-C viremia tended to worsen rather than improve mortality among the co-infected patients (Brust et al 2002).…”
mentioning
confidence: 99%
“…In that study, researchers also found an intermediate protective role for antibodies specific for the E2 protein of GBV-C. Studies conducted in the highly active antiretroviral therapy (HAART) era have demonstrated that GBV-C is associated with lower rates of HIV rebound after HAART-driven virological success (Antonucci et al 2005, Souza et al 2006. Several mechanisms have been proposed to explain the putative effect of GBV-C on the course of HIV disease, such as increased secretion of the chemokines regulated on activation, normal T cell expressed and secreted (Nattermann et al 2003), macrophage inflammatory protein (MIP)-1α, MIP-1β and stromal cell-derived factor-1, reduced expression of the chemokine receptors CCR5 and CXCR4 (Xiang et al 2004), preservation of the Th1 cytokine profile (Sathar et al 2004), activation of the interferon (IFN) gene system (Capobianchi et al 2006), increased frequency of plasmacytoid dendritic cells expressing CD80 (Lalle et al 2008) and decreased T cell activation (Maidana-Giret et al 2009). In contrast, other studies have failed to demonstrate an influence of GBV-C on the course of HIV infection (Quiros-Roldan et al 2002, Jung et al 2005, Van der Bij et al 2005, Haji Molla Hoseini et al 2007), while at least one report concluded that GBV-C viremia tended to worsen rather than improve mortality among the co-infected patients (Brust et al 2002).…”
mentioning
confidence: 99%
“…This effect may reduce a successful HIV-1 interaction with infected cell (Xiang, 2004). Several lines of evidence suggest a possible inhibition of HIV-1 by GBV-C through increase in soluble ligands for HIV-1 correceptor and activation of innate immunity (Lalle, 2008;Mohr & Stapleton, 2009). In addition, the beneficial effect of GBV-C on survival of HIV-1 infected patients might be genotype specific (Schwarze-Zander et al, 2006).…”
Section: Hiv Co-infectionmentioning
confidence: 99%
“…Recent studies showed that HIV-1 patients coinfected with GBV-C have a higher percentage of CD80 + mature pDCs, which might contribute to effective control of HIV-1 [50]. Evidence also exists that GBV-C infection in HIV-infected patients could lead to the activation of IFN genes [19]. Investigations of GBV-C-positive and GBV-C-negative HIV-infected patients showed that the expression of IFN genes 2-5-OAS, MxA, IFN AR-1, and PKR were relatively increased in HIV-GBV-C coinfected cases.…”
Section: Gbv-c Down-regulates Chemokine Receptors To Interfere With Hmentioning
confidence: 99%
“…Recent reports are also suggestive of improved initial response to antiretroviral regimens [17] and sustained suppression of HIV viral loads for prolonged periods [18]. Studies also associate the role of GBV-C in increasing interferon-γ (IFN-γ) and plasmacytoid dendritic cell (pDC) maturation to mediate innate antiviral immune responses in the host [19,20]. The disease attributes underlying HIV-1/GBV-C coinfection need to be discussed in detail; therefore, we reviewed the published literature for recent research findings on the pathophysiology of GBV-C infection and its impact on HIV disease progression.…”
Section: Introductionmentioning
confidence: 99%